Effectiveness of chitosan/propolis extract emulsion coating on refrigerated storage quality of crayfish meat (Astacus leptodactylus) - coban, Mehmet Zulfu (Taylor & Francis Ltd, 2021)
In this study, propolis extract emulsions were used in chitosan coatings to keep the storage quality of crayfish meat during shelf-life (16 days). Crayfish meats were coated with a solution of chitosan containing propolis extract emulsions (0.3 and 0.6% v/v) and then stored at 4 C. Coatings protective effectiveness was determined by chemical analyses (pH, Thiobarbituric acid, Peroxide value, Total volatile basic nitrogen, and K values), microbiological (Total aerobic mesophilic bacteria, Psychrotrophic bacteria H2S-producing bacteria, Yeasts- Moulds), and sensorial attributes (Odor, Taste, Firmness and Overall acceptance). Results demonstrate that chitosan coatings containing propolis extract are effective in controlling the growth of bacteria and chemical indices. These results can be beneficial for seafood processing sectors, as well as for food technologists.
Eficacia del recubrimiento de la emulsión de extracto de quitosano/propóleo en la calidad de la carne de cangrejo de río (Astacus leptodactylus) en almacenamiento refrigerado
Keywords: Chitosan-based coating; propolis extract emulsion; shelf life; crayfish (Astacus leptodactylus)